2022
DOI: 10.1088/1361-6463/ac4294
|View full text |Cite
|
Sign up to set email alerts
|

Active species evolution in the presence of different targets impacted by a helium plasma jet at atmospheric pressure

Abstract: A low-temperature plasma jet is generated by a dielectric barrier discharge poweredby a pulsed high voltage in helium flow (3 L/min) at atmospheric pressure inpresence of different targets (glass slide or ultra-pure water or a grounded metal plate)positioned perpendicular to the plasma propagation axis. Experimental electricalcharacterizations as discharge current, voltage and powerand optical ones as intensifiedcamera ICCD, Schlieren imaging and emission spectroscopy to follow specific excitedspecies have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…As in their results, the OH-LIF intensity was found to be much higher for the metal and the water surface compared to the glass plate. Previously, we reported the evolution of radiative excited species (OH * , N * 2 ) during a voltage pulse, while a He-APPJ impacted various targets [31]. It was found that the regions of the detected excited OH * radicals were the same as the regions where we observed, in the present work, ground state OH radicals.…”
Section: Spatially Resolved Oh Densities In Contact With a Targetsupporting
confidence: 81%
See 4 more Smart Citations
“…As in their results, the OH-LIF intensity was found to be much higher for the metal and the water surface compared to the glass plate. Previously, we reported the evolution of radiative excited species (OH * , N * 2 ) during a voltage pulse, while a He-APPJ impacted various targets [31]. It was found that the regions of the detected excited OH * radicals were the same as the regions where we observed, in the present work, ground state OH radicals.…”
Section: Spatially Resolved Oh Densities In Contact With a Targetsupporting
confidence: 81%
“…It is also partly the case for the ultra-pure surface but with a less important surface spreading than on glass surface because a part of the plasma discharge remains in the volume as a small conductive channel, while for the metal, there is mainly the formation of a stronger volumic conductive channel between the surface and the tube outlet. These effects linked to the nature of the surfaces are already detailed in our previous paper [31] and can therefore explain the differences observed between pLIF signal intensities in the case of the lower permittivity surfaces (glass and water) and the highest one (metal).…”
Section: Temporal Distribution Of Oh Plif Intensity After the Dischar...supporting
confidence: 55%
See 3 more Smart Citations